A Modified Surgical Method Combined with Blepharoplasty Design for Treatment of Xanthelasma Palpebrarum. (30th November 2020) - Choi, Eun Jeong; Oh, Tea Min; Han, Hyun Ho
Abstract : Purpose . Xanthelasma palpebrarum manifests as a yellowish placoid on the medial aspect of the upper eyelids, often in middle and old age. Aggravated lateral hooding of the eyelid might cause a deformity with conventional surgery, which appears to be more deficient on the medial side with excess hooding of the lateral skin. The authors suggest a novel surgical technique to solve this problem and reconstruct the defect appropriately. Methods . From July 2017 to December 2018, our method of combining excision with blepharoplasty was performed on 8 patients, consisting of 15 lesions on the upper eyelid and 6 lesions on the lower lid. Lesion removal incorporating blepharoplasty incision was done. After resection, the orbicularis oculi musculocutaneous flap was widely elevated extending through the whole upper eyelid with the lateral flap first along with fat maneuver. The flap was advanced into the defect, with even distribution of tension, after lower flap fixation to the required height of the eyelid fold. Taping was done with a hydrocolloid bandage and kept for 2 weeks. Results . The wounds were healed primarily, and no cases of recurrence, lagophthalmos, hypertrophic scar, pigmentation, or remarkable deformity were noted. All patients were satisfied, and the functional outcomes were excellent. Two patients had trivial complications specific to our method, that of triple fold and neo-Mongolian fold, which were simply revised later. Conclusions . This modality overcame the drawbacks of eyelid deformity observed in previous surgical methods, giving excellent results without any critical complications.